Draft Annual Plan 1984-85 Sixth Five Year Plan 1980-85 Centrally Sponsored Schemes Union Territory of Pondicherry - Planning Commission (Planning Commission, 1984)
Sixth Plan Outlay for the Centrally Sponsored Scheme and Central Sector Schemes have not been indicated as they are yet to be received from Government of India. Approved outlay for 1983-84 have been indicated only for the schemes for which provision exist in the budget document of 1983-84 Only token provision has been proposed for the scheme numbers 5 and 8 in the absence of specific sanction from Government, of India for the operation of these schemes.
Government of Pondicherry Planning and Research Department